The Antibacterial Effects of Supermolecular Nano-Carriers by Combination of Silver and Photodynamic Therapy - Feng, Gui-ning; Huang, Xiao-tao; Jiang, Xin-lin; Deng, Ting-wei; Li, Qiu-xia; Li, Jie-xia; Wu, Qian-ni; Li, Song-pei; Sun, Xian-qiang; Huang, Yu-gang; Qin, Ai-ping; Liang, Lu; et al. (Frontiers in Chemistry, 2021)
The over-use of antibiotics has promoted multidrug resistance and decreased the efficacy of antibiotic therapy. Thus, it is still in great need to develop efficient treatment strategies to combat the bacteria infection. The antimicrobial photodynamic therapy (aPDT) and silver nanoparticles have been emerged as effective antibacterial methods. However, the silver therapy may induce serious damages to human cells at high concentrations and, the bare silver nanoparticles may rapidly aggregate, which would reduce the antibacterial efficacy. The encapsulation of sliver by nano-carrier is a promising way to avoid its aggregation and facilitates the co-delivery of drugs for combination therapy, which does not require high concentration of sliver to exert antibacterial efficacy. This work constructed a self-assembled supermolecular nano-carrier consisting of the photosensitizers (PSs), the anti-inflammatory agent and silver. The synthesized supermolecular nano-carrier produced reactive oxygen species (ROS) under the exposure of 620-nm laser. It exhibited satisfying biocompatibility in L02 cells. And, this nano-carrier showed excellent antibacterial efficacy in E. coli and S. aureus as indicated by bacterial growth and colony formation. Its antibacterial performance is further validated by the bacteria morphology through the scanning electron microscope (SEM), showing severely damaged structures of bacteria. To summary, the supermolecular nano-carrier TCPP-MTX-Ag-NP combining the therapeutic effects of ROS and silver may serve as a novel strategy of treatment for bacterial infection.